2012
DOI: 10.1590/s1678-77572012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tissue reaction to Aroeira (Myracrodruon urundeuva) extracts: a histologic and edemogenic study

Abstract: ObjectivesThis study evaluated subcutaneous tissue response to Aroeira (Myracrodruon urundeuva) extract employing edemogenic and histological analyses. Material and methodsTest groups consisted of aqueous and ethanolic Aroeira extracts and saline (control). For edema quantification, 18 rats received an intravenous injection of Evan's Blue. After 30 min, the extracts and saline were injected on the dorsum of the rats, which were then sacrificed after 3 and 6 h. Readings were performed in a spectrophotometer. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
(11 reference statements)
3
22
0
3
Order By: Relevance
“…Different doses (extract concentration) might determine the effect in a positive, or negative manner. In general, low concentrations of "aroeira" extract do not promote cell death and are biocompatible in different experimental models (Nunes Jr. et al 2008;Machado et al 2012;Machado and Oliveira 2014), as confirmed by the present results. In the present study, the high values of cell viability at lower concentrations in 48 h could be an effect of some components of the extract, such as glucose molecules from tannins and flavonoid (Souza 2012;Machado et al 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Different doses (extract concentration) might determine the effect in a positive, or negative manner. In general, low concentrations of "aroeira" extract do not promote cell death and are biocompatible in different experimental models (Nunes Jr. et al 2008;Machado et al 2012;Machado and Oliveira 2014), as confirmed by the present results. In the present study, the high values of cell viability at lower concentrations in 48 h could be an effect of some components of the extract, such as glucose molecules from tannins and flavonoid (Souza 2012;Machado et al 2015).…”
Section: Discussionsupporting
confidence: 86%
“…These in vitro tests employing cell culture are advantageous due to their simplicity/quickness, low costs (Freshney 2005), and control of the some experimental conditions (pH, CO 2 concentration, and levels of some molecules) (Schweikl and Schmalz 1996;De Deus et al 2009). In general, there are contradictory results involving "aroeira" due to tissue biocompatibility (Nunes Jr. et al 2008;Machado et al 2012) and the induction of apoptosis in cellular lineages (Ferreira et al 2011). However, comparision of these works with the present results showed some similarities between them.…”
Section: Discussionsupporting
confidence: 64%
“…Sabemos ainda que as plantas contem inúmeros constituintes e seus extratos podem apresentar efeitos sinérgicos entre os diferentes princípios ativos devido à presença de compostos de classes ou estruturas diferentes contribuindo para a mesma atividade (Maciel et al, 2002). A integração destas áreas na pesquisa de plantas medicinais conduz um caminho promissor e eficaz para descobertas de novos medicamentos.…”
Section: Perspectivas Futurasunclassified
“…Chalcones and dihydrochalcones belong to the class of flavonoids which, apart from their antioxidant activity, are known for their ability to strengthen capillary walls, thus assisting circulation and helping to prevent and treat bruising, varicose veins, bleeding gums and nosebleeds. In vitro, catechins are involved in antimicrobial, antioxidant activity and anti-inflammatory effects in this species (Viana et al, 2003;Sá et al, 2009;Machado et al, 2012). Still when being reported on the use of aroeira in accent baths against vaginal itching, it is used to boil its shells by women in post-partum baths, such as cicatrizant and anti-inflammatory (Silvino, 2014).…”
Section: Introductionmentioning
confidence: 99%